For-Profit Education: The Sleep of Ethical Reason - Natale, Samuel M. 19XX- (Journal of business ethics, 2015)
This article argues the philosophical concerns and foundational challenges raised by a for-profit model of education. The for-profit model is governed by a business paradigm, without reference to the context in which it is found. The authors explore primary ethical questions and challenges presented by this model. As such, they present potential solutions to the growing problem in higher education as a corporate entity. The authors introduce a potential model for analysis of the issues and suggest an interventional technique with concrete directions for change. Universities are on the threshold of a transformation which can no longer be isolated from wider society. This environment awakened the critical task of blending corporate success with educational integrity.